Quantifiers and Variables: Insights from Sign Language (ASL and LSF) - Philippe Schlenker (The Baltic International Yearbook of Cognition, Logic and Communication, 2010)
In standard logical systems, quantifiers and variables are essential to express complex relations among objects. Natural language has expressions that have an analogous function: some noun phrases play the role of quantifiers (e.g. every man), and some pronouns play the role of variables (e.g. him, as in Every man likes people who admire him). Since the 1980’s, there has been a vibrant debate in linguistics about the way in which pronouns come to depend on their antecedents. According to one view, natural language is governed by a ‘dynamic’ logic which allows for dependencies that are far more flexible than those of standard (classical) logic. According to a competing view, the treatment of variables in classical logic does not have to be fundamentally revised to be applied to natural language. While the debate centers around the nature of the formal links that connect pronouns to their antecedents, these links are not overtly expressed in spoken language, and the debate has remained open. In sign language, by contrast, the connection between pronouns and their antecedents is often made explicit by pointing. We argue that data from French and American Sign Language provide crucial evidence for the dynamic approach over one of its main classical competitors; and we explore further sign language data that can help choose among competing dynamic analyses. References Bahan, B., Kegl, J., MacLaughlin, D. & Neidle, C. 1995. ‘Convergent Evidence for the Structure of Determiner Phrases in American Sign Language’. In L. Gabriele, D. Hardison & R. Westmoreland (eds.) ‘FLSM VI, Proceedings of the Sixth Annual Meeting of the Formal Linguistics Society of Mid-America, Volume Two’, 1–12. Bloomington, IN: Indiana University Linguistics Club Publications. Brasoveanu, A. 2006. Structured Nominal and Modal Reference. Ph.D. thesis, Rutgers, The State University of New Jersey. Brasoveanu, A. 2010. ‘Decomposing Modal Quantification’. Journal of Semantics 27, no. 4: 129–209. Chomsky, N. 1957. Syntactic Structures. The Hague/Paris: Mouton. Chomsky, N. 1965. Aspects of the Theory of Syntax. Cambridge, Massachusetts: MIT Press. Chomsky, N. 1981/1993. Lectures on Government and Binding: The Pisa Lectures. Mouton de Gruyter. Dekker, P. 2004. ‘Cases, adverbs, situations and events’. In H. Kamp & B. Partee (eds.) ‘Context-dependence in the Analysis of Linguistic Meaning’, 383–404. Elsevier. Elbourne, Paul. 2005. Situations and Individuals. MIT Press. Emmorey, K. 2002. Language, cognition, and the brain: Insights from sign language research. Erlbaum. Evans, G. 1980. ‘Pronouns’. Linguistic Inquiry 11: 337–362. Fox, D. 2003. ‘On Logical Form’. In H. Randall (ed.) ‘Minimalist Syntax’, 82–123. Blackwell. Gamut, L. T. F. 1991. Logic, Language and Meaning. Chicago University Press. Geach, P. 1962. Reference and Generality: An Examination of Some Medieval and Modern Theories. Ithaca, New York: Cornell University Press. Groenendijk, J. & Stokhof, M. 1991. ‘Dynamic Predicate Logic’. Linguistics and Philosophy 14, no. 1: 39–100. http://dx.doi.org/10.1007/BF00628304 Heim, I. 1982. The Semantics of Definite and Indefinite Noun Phrases. Ph.D. thesis, University of Massachusetts Amherst. Heim, I. 1990. ‘E-Type Pronouns and Donkey Anaphora’. Linguistics and Philosophy 13: 137–177. http://dx.doi.org/10.1007/BF00630732 Heim, I. & Kratzer, A. 1998. Semantics in Generative Grammar. Blackwell. Kamp, H. 2003. ‘A Theory of Truth and Semantic Representation’. In J. Groenendijk, T. Janssen & M. Stokhof (eds.) ‘Minimalist Syntax’, 277–322. Dordrecht. Reprint. Kamp, H. & Reyle, U. 1993. From Discourse to Logic. D. Reidel, Dordrecht. Lasnik, H. 1989. Essays on anaphora. Dordrecht: Reidel. Lillo-Martin, D. 1991. Universal Grammar and American Sign Language: Setting the Null Argument Parameters. Kluwer Academic, Boston, MA. http://dx.doi.org/10.1007/978-94-011-3468-2 May, R. 1985. Logical Form. Cambridge, MA: MIT Press. Montague, R. 1974. Formal Philosophy. Selected Papers by Richard Montague. New Haven. Edited by R. Thomason. Neidle, C., Kegl, J., MacLaughling, D., Bahan, B. & Lee, R. G. 2000. The Syntax of American Sign Language: Functional Categories and Hierarchical Structure. Cambridge, MA: MIT Press. Nouwen, R. 2003. ‘Plural pronominal anaphora in context’. Number 84 in Netherlands Graduate School of Linguistics Dissertations, LOT, Utrecht. Quine, W. V. O. 1987. ‘Variables’. In ‘Quiddities. An Intermittently Philosophical Dictionary’, Belknap Press. Reinhart, T. 1976. The Syntactic Domain of Anaphora. Ph.D. thesis, MIT. Sandler, W. & Lillo-Martin, D. 2006. Sign Language and Linguistic Universals. Cambridge University Press. Schlenker, P. to appear. ‘Donkey Anaphora: the View from Sign Language’. Accepted for publication with minor revisions in Linguistics & Philosophy. Sinha, S. 2009. A Grammar of Indian Sign Language. Ph.D. thesis, Jawaharlal Nehru University, New Delhi, India. Stone, M. 1992. ‘Or and Anaphora’. Proceedings of SALT 2 367–385. van den Berg, M. 1996. Some aspects of the internal structure of discourse: the dynamics of nominal anaphora. Ph.D. thesis, ILLC, Universiteit van Amsterdam.